FAKTOR-FAKTORYANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA PROGRAMSTUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS KHAIRUN TERNATE - Ismira Usman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2015)
This study aims to determine the effect of learning motivation, learning and campuslearning environment partially or simultaneously. The population in this study were all students ofthe Faculty of Management Studies EconomicsUniversity Khairun Ternate half of 4 (four), 6 (six),and 8 (eight) with a population of 245 students. The sampling technique using stratified randomsampling method or conditional random method. To determine the number of samples to be taken,the researchers used a formula slovin thus obtained 71 students who will be used as samples. Datacollection techniques used is to deploy a questionnaire, interview, observation and literature study.Analysis of the data in this study is using multiple regression analysis (multiple regression analysis).The results using SPSS 19 is obtained regression equation Y =-0.489 + 0,461X1 +0,581X2 + 0,092X3. Where learning motivation variable (X1), interest in learning (X2) and thecampus learning environment (X3) positive and significant impact on student achievementmanagement courses economics faculty either partially or simultaneously, which means that Haisaccepted and so the hypothesis is rejected H0submitted can be verified that the hypothesis isaccepted.